Cultural Histories of Democracy Studies in Political Culture Since the 19th Century - Germany and Beyond - Mergel, Thomas (London Routledge, 2026)
Over the last two decades German political history has changed fundamentally. It has reinvented itself as cultural history and sought to apply symbolic, linguistic, and praxeological approaches.This book brings for the first time in English, Thomas Mergels inquiries into the history of democracy in Germany, with comparative perspective across the 19th and 20th centuries, while offering frequent sideways glances at its Western European and American neighbors. Politics is highlighted as a social and symbolic practice; the body, language, symbolism, and routine action are examined as factors that let politics emerge as a process of communication.The contributions in this volume have been written over the past 25 years, with two previously unpublished chapters. They are intended to make the largely German discussion more visible on an international level and to show the application of theoretical concepts. By concentrating on parliamentary politics, parties, and elections, the book not only studies political practices and forms of communication but also deciphers political mentalities in order to historicize "democracy" as a political concept. Against the background of the German experience during the 20th century, the democratic culture of the Weimar Republic occupies a special place.
Introduction: Cultural History of Politics ReconsideredSection I - Mass Politicisation and the Political Mass Market c. 1850-1914Fraud, Rioting, Vote-Buying. European Election Cultures in Transition to the Political Mass Market, 1860-1914Counter-Image, Role Model, and Specter. American Parties in the Perception of the German Political Public, 1890-1920Section II - The Weimar Republic: Democracy in a Divided SocietyThe Weimar Reichstag as a Social Space Highly Esteemed Mister Colleague . On the Symbolic Dimensions of Speech in the Reichstag of the Weimar RepublicIn Search of a Good Polity. Structures of Political Expectation in the Weimar RepublicThe Failure of German Tory Conservatism. The Conversion of the DNVP into a Radical Right-Wing Party 1928-1932Section III - Political Communication and Conflict after 1945The Unknown and the Familiar Enemy. The Semantics of Anti-Communism in the USA and Germany, 1945-75Objectivity and Fairness. Negative Campaigning, Rule-Breaking, and Rule Discourse in German Electioneering 1949-1990Time of Strife. Democracy and Conflict in 1970s Germany
E-Book / Zugriff nur im Lesesaal